Contractual solutions to the holdup problem: a survey - Paulo, Cinthia Konichi (2011)
In this survey, we presented the general idea and main results from what we understand that are the most important contributions to contractual solutions to the holdup problem literature. The aim of this paper is to push the previous analysis, uniform the notation and provide a snapshot on the most recent literature, as well as bring topics for future inquires on this issue.